Behavior of GFRP-Wood Composite Sandwich Beam-Column Joints with Angle Steels. (30th July 2020) - Xie, ZhiJin; Qi, YuJun; Fang, Hai; Liu, WeiQing
Abstract : In this paper, a new type of connection system was proposed for joints between GFRP-wood composite sandwich beams and columns which were made of glass fiber-reinforced polymer (GFRP) face sheets and southern pine wood cores. The connection system comprised steel angles anchored to the column, and the beam was bolted to the angles. Six different connection system configurations were tested to understand the static behavior of the connection system under different parameters including the length of the beam-closed limb and the presence of ribs. The failure modes of the connection system obtained in tests were of three types: yield failure of the angle steels, local crushing failure of the GFRP-wood composite sandwich beam, and tensile failure of the bolt on the beam-closed limb. The initial rotational stiffness values of the three specimens with ribs were 113.75%, 119.56%, and 227.94% higher than the corresponding three specimens without ribs. And the ductility of connection improved by up to 30.28% due to the presence of stiffener ribs. Based on the tests, the bearing capacity and stiffness of the connection system were predicted. For the specimens without ribs, the method in Eurocode 3 was adopted for bearing capacity and stiffness predictions. For the specimens with ribs, a mechanical model was established for bearing capacity and initial stiffness predictions, which was solved according to the corresponding stress features and failure modes. The analytical results were in good agreement with the experimental results.